Numerical Methods for Reliability and Safety Assessment Multiscale and Multiphysics Systems - Kadry, Seifedine; El Hami, Abdelkhalak (Springer International Publishing : Imprint: Springer, 2015)
This book offers unique insight on structural safety and reliability by combining computational methods that address multiphysics problems, involving multiple equations describing different physical phenomena, and multiscale problems, involving discrete sub-problems that together  describe important aspects of a system at multiple scales. The book examines a range of engineering domains and problems using dynamic analysis, nonlinear methods, error estimation, finite element analysis, and other computational techniques. This book also: ·       Introduces novel numerical methods ·       Illustrates new practical applications ·       Examines recent engineering applications ·       Presents up-to-date theoretical results ·       Offers perspective relevant to a wide audience, including teaching faculty/graduate students, researchers, and practicing engineers.